Decorative Finishing Metal Artwork - Naimov Sanjar Tulkunovich (International Journal on Orange Technologies, 2022)
The article deals with topical issues of the use of decorative finishes and restoration of sculptures made of copper and bronze alloys with a brief summary of it.